Ethnic diversity and inequality in sub-Saharan Africa: Do institutions reduce the noise? - Kazeem Bello Ajide; Olorunfemi Y. Alimi; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
Studies on the causes of income differences between the rich and the poor have received an extensive attention in the inequality empirics. While ethnic diversity h asalso been identified as one of the fundamental causes of income inequality, the role of institutions as a mediating factor in the ethnicity-inequality nexus has not received the scholarly attention it deserves. To this end, this study complements the existing literature by investigating the extent to which institutional framework corrects the noisy influence originating from the nexus between "ethnic diversity" and inequality in 26 sub -Saharan African countries for the period 1996-2015. The empirical evidence is based on pooled OLS, fixed effects and system GMM estimators. The main findings reveal that the mediating influences of institutional settingsaredefective, thus making it extremely difficult to modulatethe noisy impacts of ethno-linguistic and religious heterogeneity on inequality. In addition, the negative influencesorchestrated by ethnolinguistic and religious diversities on inequality fail toattenuate the impact of income disparityeven when interacted with institutions. On the policy front, institutional reforms tailored toward economic, political and institutional governances should be targeted.
Keywords: C23; D02; D63; E02; 330; Linguistic; religious; ethnicity; inequality; Institutions; Kuznets curve